if tan theta equals to a /b prove that aSin theta minus b cos theta divided by asin theta + b cos theta equals to a square minus b square divided by a square + b square
Answers
Step-by-step explanation:
We have given that,
Tan Θ = a / b; (i)
We asked to prove that,
(a sinΘ - b cosΘ) / (a sin Θ + b cosΘ) = . (ii)
So, divide the numerator and the denominator by cos Θ of the LHS of equation (ii);
⇒ {(a sinΘ - b cosΘ) / cosΘ } / {(a sin Θ + b cosΘ) / cosΘ}
∴As we know that when divide any number both in the numerator and denominator on a fraction then its value will be equal.
Hence, this will give us,
⇒ {a tan Θ - b} / {a tan Θ + b}; (iii)
Now, put the value of Tan Θ in equation (iii) from equation (ii),
⇒{a * a/b - b} / {a * a/b + b};
⇒{ / b - b} / {
/ b + b} ;
⇒ {( -
) / b } / {(
+
) / b }
From here b will cancel out,
Therefore, ⇒ ( -
) / (
+
);
⇒ .
Hence, proved.
That's all
Refers to attachment ☆~
![](https://hi-static.z-dn.net/files/d13/7b71d26137fb832591ffb6000a5bc43f.jpg)
![](https://hi-static.z-dn.net/files/dac/00facb3d2acccca3024383cbd0e85e73.jpg)